PENGARUH BRAND IMAGE PRODUK SCARLETT TERHADAP KEPUTUSAN PEMBELIAN REMAJA PUTRI - veronica; Youra Putri Anindari; Rayhan Gunaningrat (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this research is: (1) to determine the influence of the brand image of Scarlett products. (2) to determine purchasing decisions among young women. In the research it is known that brand image and purchasing decisions of young women. This research method is quantitative, the data collection technique used in this research is Probability Sampling. The population in this study consisted of 90 respondents who came from young women who used Scarlett products. Data processing in this research uses SPSS version 25. Keywords: Brand Image, Purchase Decision